300 : rise of an empire [videorecording (DVD)] - Stapleton, Sullivan; Green, Eva, 1980-; Headey, Lena; Miller, Frank, 1957- (Warner Home Video, 2014)
Greek general Themistokles attempts to unite all of Greece by leading the charge that will change the course of the war. He's pitted against the massive invading Persian forces led by mortal turned god Xerxes, and Artemesia, vengeful commander of the Persian navy.